Unveiling the Interplay Between Dendritic Cells and Natural Killer Cells as Key Players in Leishmania Infection - Ana Valério-Bolas; Mafalda Meunier; Armanda Rodrigues; Joana Palma-Marques; Rui Ferreira; Inês Cardoso; Lis Lobo; Marta Monteiro; Telmo Nunes; Ana Armada; Wilson T. Antunes; Graça Alexandre-Pires; et al. (Journal of Immunology Research, 2025)
Leishmaniasis is a group of parasitic diseases whose etiological agent is the protozoa Leishmania. These diseases afflict impoverished populations in tropical and subtropical regions and affect wild and domestic animals. Canine leishmaniasis is a global disease mostly caused by L. infantum. Dogs are recognized as a good reservoir since harbor the infection long before developing the disease, facilitating parasite transmission. Furthermore, there is growing evidence that dogs may also be the reservoir of the American Leishmania spp. as L. amazonensis. The innate immune response is the first defense line against pathogens, which includes natural killer (NK) and dendritic cells (DCs). By recognizing and ultimately destroying infected cells, and by secreting immune mediators that favor inflammatory microenvironments, NK cells take the lead in the infectious process. When interacting with Leishmania parasites, DCs become activated and play a key role in driving the host immune response. While activated DCs can modulate NK cell activity, Leishmania parasites can directly activate NK cells by interacting with innate immune receptors. Once activated, NK cells can engage in a bidirectional interplay with DCs. However, the complexity of these interactions during Leishmania infection makes it challenging to fully understand the underlying processes. To further explore this, the present study investigated the dynamic interplay established between monocyte-derived DCs (moDCs) and putative NK (pNK) cells of dogs during Leishmania infection. Findings indicate that the crosstalk between moDCs exposed to L. infantum or L. amazonensis and pNK cells enhances chemokine upregulation, potentially attracting other leukocytes to the site of infection. pNK cells activated by L. infantum infected DCs upregulate IL-10, which can lead to a regulatory immune response while moDCs exposed to L. amazonensis induced pNK cells to overexpress IFN-γ and IL-13, favoring a mix of pro- and anti-inflammatory response. In addition, parasite-derived extracellular vesicles (EVs) can modulate the host immune response by stimulating the upregulation of anti-inflammatory cytokines and perforin release, which may impact infection outcomes. Thus, Leishmania and parasitic EVs can influence the bidirectional interplay between canine NK cells and DCs.